Role of polymerase chain reaction–based viral detection in pterygia - Janani Madhuravasal Krishnan; Rama Rajagopal; Dhanurekha Lakshmipathy; Shweta Agarwal; A R Anand; Lily Therese; Aishwarya Thangam; Hajib Narahari Rao Madhavan (Indian Journal of Ophthalmology, 2023)
Purpose: Pterygium is a fibrovascular disease that originates in the conjunctiva and commonly spreads to the corneal surface, thereby posing a threat to eyesight. Despite intensive research, the pathophysiology of this disease remains unclear. Recent research suggests that oncogenic viruses, such as human papillomavirus (HPV), cytomegalovirus, and Epstein–Barr virus (EBV), may play a role in pterygia development. Although there are questions concerning the function of oncogenic viruses in pterygium pathogenesis, existing research shows a lack of consensus on the subject, demonstrating the heterogeneity of pterygium pathophysiology. Therefore, we aimed to simultaneously detect the three common viral pathogens that have been reported in pterygium tissue obtained after excision. Methods: Thirty-five tissue specimens of pterygium from patients undergoing pterygium surgery (as cases) were analyzed for evidence of viral infection with multiplex polymerase chain reaction (PCR), and virus-specific real-time quantitative PCR was used for the samples that were detected positive by multiplex PCR. Results: Of the 35 patients, one sample was positive for EBV and two samples were positive for HPV. Further PCR-based DNA sequencing of the HPV PCR-positive product showed identity with HPV-16. Real-time quantitative PCR on samples that showed EBV or HPV positivity did not yield any detectable copy number. Conclusion: Our study results confirmed that PCR positivity could be due to transient flora, but it was not quantitatively significant to conclude as the causative factor of pterygium pathogenesis. However, additional studies with larger sample populations are warranted to fully determine the role of the virus in pterygium.